Structural abnormalities in the thalamus of migraineurs with aura: A multiparametric study at 3 T. Issue 4 (1st March 2013) - Granziera, Cristina; Daducci, Alessandro; Romascano, David; Roche, Alexis; Helms, Gunther; Krueger, Gunnar; Hadjikhani, Nouchine
<x xml:space="preserve">Abstract</x> Background and objectives: The thalamus exerts a pivotal role in pain processing and cortical excitability control, and migraine is characterized by repeated pain attacks and abnormal cortical habituation to excitatory stimuli. This work aimed at studying the microstructure of the thalamus in migraine patients using an innovative multiparametric approach at high‐field magnetic resonance imaging (MRI). Design: We examined 37 migraineurs (22 without aura, MWoA, and 15 with aura, MWA) as well as 20 healthy controls (HC) in a 3‐T MRI equipped with a 32‐channel coil. We acquired whole‐brain T1 relaxation maps and computed magnetization transfer ratio (MTR), generalized fractional anisotropy, and T2* maps to probe microstructural and connectivity integrity and to assess iron deposition. We also correlated the obtained parametric values with the average monthly frequency of migraine attacks and disease duration. Results: T1 relaxation time was significantly shorter in the thalamus of MWA patients compared with MWoA (P < 0.001) and HC (P ≤ 0.01); in addition, MTR was higher and T2* relaxation time was shorter in MWA than in MWoA patients (P < 0.05, respectively). These data reveal broad microstructural alterations in the thalamus of MWA patients compared with MWoA and HC, suggesting increased iron deposition and myelin content/cellularity. However, MWA and MWoA patients did not show any differences in the thalamic nucleus involved in pain processing in migraine. Conclusions: There are broad microstructural alterations in the thalamus of MWA patients that may underlie abnormal cortical excitability control leading to cortical spreading depression and visual aura. Hum Brain Mapp 35:1461–1468, 2014. © 2013 Wiley Periodicals, Inc.